The effect of PjBl model on creative thinking ability and higher-order cognitive outcomes in high school - Ricky Prananta Ginting; Ervan Johan Wicaksana; Desfaur Natalia (University of Muhammadiyah Malang, 2024)
Creative thinking skills are demans on 21st century competencies, and this is an ability that students must have in the independent curriculum. Cognitive learning outcomes are a form of achievement of students’ knowledge after learning. This research aims to analyze the effect of the project-based learning model on the creative thinking ability and cognitive learning outcomes of students at Senior High School 11 Muaro Jambi. The research design used Pretest-Posttest Non-Equivalent Control Group Design. The research sample consisted of 58 students of class XI Phase F students taken by purposive sampling. Data obtained through observation and tests. Data analysis using One Way MANCOVA to verify hypothesis data. The results showed that the average creative thinking ability and cognitive learning outcomes in project-based learning were higher than problem-based learning. The results of the analysis concluded that the use of project-based learning model affects the creative thinking ability and cognitive learning outcomes of students. Therfore, the project-based learning model is recommended to be applied to support the implementation of the independent curriculum in high school as an effort to maximize learning.